(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article provides information about the expression (meaning) in the subtext of stylistic media in a literary text, nuances hidden by the author, a hidden idea or meaning in a literary text, revealing the subtext, the general ideological meaning of the text, the main meanings of stylistic means are considered.